Effectiveness of an interactive nutrition education kit on mothers’ knowledge and attitudes toward stunting prevention: a quasi-experimental study - Az Zahra Nur Ainiyyah; Tri Siswati; Waluyo; Almira Sitasari; Muhammad Abdul Halim Ar-Rasyid; Jutharat Attawet (Berita Kedokteran Masyarakat, 2026)
Purpose: This study aimed to evaluate the effectiveness of KIT DENTING, an interactive multimodal nutrition education kit, in improving mothers’ knowledge and attitudes toward stunting prevention compared with conventional leaflet-based education. Methods: A quasi-experimental study with a nonequivalent pre–post-test control group design was conducted among 60 mothers of children aged 0–23 months in the working area of Pakem Primary Health Center, Sleman Regency, Yogyakarta. Participants were assigned to an intervention group that received nutrition education using KIT DENTING or a control group that received leaflet-based education. Knowledge and attitudes were assessed at baseline (pre-test), 1 week after the intervention (post-test 1), and 4 weeks after the intervention (post-test 2). Data were analyzed using paired and independent statistical tests to examine within- and between-group differences. Results: Both groups showed significant improvements in knowledge following the intervention. In contrast, the intervention group demonstrated greater and more sustained improvements in knowledge and attitudes at both follow-up points. Compared with the control group, the intervention group sustained knowledge gains and showed improvements in attitudes, but with reduced effect consistency at four weeks of follow-up. Conclusion: Nutrition education using the interactive multimodal KIT DENTING was more effective than leaflet-based education in improving and sustaining mothers’ knowledge and attitudes toward stunting prevention. These findings support the integration of interactive, multimodal nutrition education tools into community-based IYCF and stunting-prevention programs at the primary health care level.